PENGARUH NILAI INDIVIDU TERHADAP NILAI ORGANISASI DENGAN NILAI SPIRITUAL SEBAGAI MEDIATOR - Kusumo, Elang; ., Sutoha; Dwi Setyorini, Albertha; Yaputra, Hermanto (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 2 (2021): Jurnal IPTA (December 2021)DO - 10.24843/IPTA.2021.v09.i02.p17, 2021)
The values of organization usually reflect the individual values of the founders, these values are recognized and preserved by members of the organization. The individual values include social values, moral values and spiritual values, which from an early age have been embedded and grow in the family and social environment. The value of the organization is also heavily influenced by the values of the individual founders. The purpose of this study is to evaluate the organizational values and the implementations into organizational activities and processes, and individual value as determinant variables which are social values, moral values and spiritual values as mediating variable. Quantitative descriptive method is used in this study, by making exposure, to explain the situation and facts found in the field, and evaluate the relationship between variables. The respondents are consisted of the employee of company in total 155 respondents. The results of this study indicated that social values and moral values as individual values, as antecedents of organizational values as well, have a positive and significant effect on organizational values. Meanwhile, between social values and organizational values through spiritual values as a mediating variable, there is a positive and insignificant effect, and between moral values and organizational values through spiritual values as a mediating variable, there is a positive and significant effect.